Improved Cuff Technique and Intraoperative Detection of Vascular Complications for Hind Limb Transplantation in Mice - Kim, Minhyung (Transplant Direct, 2018)
BACKGROUND: Vascularized composite tissue allotransplantation (VCA) from a cadaveric donor has now become a clinical reality and the treatment modality of choice for patients with devastating injuries, deformities, and complex tissue defects. However, many VCA patients experience severe toxicities due to the strong immunosuppression required secondary to high antigenicity of the grafts. To improve immunosuppressive protocols for VCA, feasible and reliable preclinical models are necessary. The purpose of this study was to introduce new techniques to an established preclinical VCA model to accelerate future investigations. METHODS: C57BL/6 (H-2(b)) and BALB/c (H-2(d)) mice were used to perform VCA as recipients and donors, respectively. Surgery time, success rate, associated complications, and mortality were analyzed. Blood flow in grafts was interrogated with laser speckle image (LSI). RESULTS: A nonsuture cuff technique was used with the abdominal aorta for end-to-end anastomosis. The cuff technique demonstrated efficiency for donor surgery (52 ± 10 minutes for donor vs. 45 ± 8 minutes for recipient surgery). Successful revascularization was achieved in 27 (90%) of 30 transplants. The majority of surgical complications occurred within 48 hours including artery occlusion, venous occlusion, cerebral stroke, and minor bleeding without mortality. LSI was useful in detecting intraoperative vascular complications with display patterns predictive of complication type. CONCLUSIONS: The described techniques may facilitate a more efficient heterotopic hind limb transplantation mouse model of VCA.